Pengaruh Penggunaan LKS IPA Terpadu Bermuatan Keterampilan Literasi Tema Gerak dalam Kehidupan Terhadap Kompetensi Siswa Kelas VIII SMPN 8 Padang - Yosa aulya putri; Asrizal Asrizal; Yulkifli Yulkifli (PILLAR OF PHYSICS EDUCATION, 2018)
In the 2013 curriculum, science teaching is conducted in integrated patter and it is supported by the school literacy movement to improve competence of students. Integrated science teaching is expected to improve three competencies of students including attitude, knowledge, and skill. However, the real conditions in school show that integrated science teaching and school literacy movement can’t implemented optimally. One solution that can be done is to use the integrated science student worksheet by integrating the skills literacy on motion theme in life. The purpose of this research was to investigate the influence of the use of Integrated science student worksheet by integrating the skills literacy of motion themes in life toward the competences of grade VIII students in SMPN 8 Padang. The type of research which conducted can be grouped into quasi experiment type with one group one group pretest-posttest design. Samples were obtained by using the purposive sampling technique. The research instruments consist of observation sheet for attitude competency, written test for knowledge competency and performance assessment for skill competency. Data analysis which used in this research consist of descriptive statistical analysis, simple linear regression analysis, significant relationship test and comparison test. Based on the result of data analysis can be stated that the use of integrated science student worksheet by integrating the skills literacy gives significant influence on the competence of knowledge and skill of grade VIII students respectively 38.44% and 35.05%. In addition, the use of integrated science student worksheet also gives a significant influence on the attitude of the grade VIII students in SMPN 8 Padang.